2020
DOI: 10.1111/1750-3841.15184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric pressure plasma jet on the physicochemical, functional, and antioxidant properties of flaxseed protein

Abstract: The aim of this study was to explore the effect of atmospheric pressure plasma jet (APPJ) on the physicochemical, functional, and antioxidant properties of flaxseed protein following APPJ treatment (0 to 240 s). The results showed that the pH value continuously dropped with the minimum value of 3.45 ± 0.15 after 240 s of APPJ treatment (–61.7%, P < 0.05). The relative protein solubility significantly declined after 15 s of APPJ treatment (–43.1%, P < 0.05), which was accompanied by the evident increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
1
36
1
Order By: Relevance
“…The contents of total phenolic acids and flavonoids in flaxseed sprouts were determined by using the Folin–Ciocalteu colorimetric method and aluminum nitrate method, respectively (Yu et al., 2020 ). The results were expressed as milligram gallic acid equivalents (GAE) and rutin/100 g of flaxseed (dry basis), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of total phenolic acids and flavonoids in flaxseed sprouts were determined by using the Folin–Ciocalteu colorimetric method and aluminum nitrate method, respectively (Yu et al., 2020 ). The results were expressed as milligram gallic acid equivalents (GAE) and rutin/100 g of flaxseed (dry basis), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The contents of total phenolic acids and flavonoids in flaxseed sprouts were determined by using the Folin-Ciocalteu colorimetric method and aluminum nitrate method, respectively (Yu et al, 2020).…”
Section: Total Phenolic Acids and Flavonoidsmentioning
confidence: 99%
“…The validated effects of plasma on proteins in solution can be roughly divided into two categories: oxidative modifications and the structural changes. Protein oxidation by plasma involves the modification of amino acid side chains [13][14][15][16], carbonylation [13,15,17], and disulfide bond cross-links [12,13,18,19]. The most pronounced side chain modifications involve the sulphonation of free sulfhydryl groups, which is also observed in treated amino acid solutions [20].…”
Section: Introductionmentioning
confidence: 99%
“…It had been demonstrated that the solubility, emulsifying and foaming properties of flaxseed protein, peanut protein, myofibrillar protein and whey protein were differently optimized following plasma treatment. 11,12 Potentially, remodeling of the spatial conformation and mild oxidation of specific amino acid residues in proteins were induced because of the formation of reactive species upon suitable plasma exposure in aqueous medium. 13 Comparatively, the polymerization of xanthan gum in solid phase, as well as the depolymerization of chitosan in acetic acid aqueous solution, had been observed following dielectric barrier discharge and high voltage pulsed discharge plasma treatments, respectively, which further optimized the emulsifying stability and hydrophilicity of these polysaccharides.…”
Section: Introductionmentioning
confidence: 99%